Improving estimates of extreme snowfalls in a spatial context. (2nd April 2013) - Balcerak, Ernie
Abstract : Mapping extreme snowfalls in mountainous areas is important for directing resources to keep roads clear and manage avalanche risk. But data in mountainous areas are sparse, with instruments often located in valleys far from areas of concern, and historical instrumental records are generally incomplete. Scientists must therefore extrapolate and interpolate from observations to estimate snowfall amounts over a region.